A PC / ABS alloy and its preparation method and application
By adding carboxylic acid-based ionomers and moisture-heat improvers to the PC/ABS alloy to form a barrier layer, the problem of deterioration of flame retardant performance of halogen-free phosphate flame retardant PC/ABS alloy under humid and heat conditions is solved, and moisture-heat aging resistance and long-term flame retardant are achieved.
Patent Information
- Application Number
- CN202310242805.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-03-14
- Publication Date
- 2025-03-25
- Estimated Expiration
- 2043-03-14
AI Technical Summary
Halogen-free phosphate flame retardant PC/ABS alloys rapidly deteriorate flame retardant under humid and heat conditions. Traditional solutions will sacrifice the melt flow and flame retardant properties of the material, resulting in defects in the construction and appearance of the part.
By adding carboxylic acid-based ionomers and moisture-heat improvers to the PC/ABS alloy, the distribution ratio is optimized to form a water molecule barrier layer/hydrolysis resistance layer, which significantly improves water permeability and moisture-heat hydrolysis resistance.
The heat-resistant aging properties and long-term flame retardant properties of phosphate flame retardant PC/ABS alloy are realized, and the inward penetration of water molecules is avoided, and the flame retardant properties and mechanical properties of the material are maintained.
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of polymer materials, and in particular to a PC / ABS alloy and a preparation method and application thereof. Background Art
[0002] Halogen-free phosphate flame-retardant PC / ABS has the characteristics of excellent mechanical properties, high fluidity and easy coloring, making it widely used in industries such as consumer electronics, automotive transportation, power tools, power supplies and adapters.
[0003] Halogen-free flame-retardant PC / ABS alloys have the problem of rapid deterioration of flame retardant properties under hot and humid conditions. The main reason is that under high temperature and high humidity conditions, moisture diffuses faster between resin molecules, and water and phosphate flame retardants undergo hydrolysis reactions, causing degradation of PC molecules, which in turn leads to deterioration of flame retardancy and mechanical properties. The traditional solution is to reduce the content of phosphate flame retardants, which will sacrifice the melt fluidity and flame retardant properties of the material, resulting in structural and appearance defects when injection molding irregular parts. In addition, there is the idea of using phenoxy polyphosphazene, which is more resistant to moisture and heat, to replace phosphate flame retardants, but this method will also reduce the fluidity of the material and increase the cost, greatly limiting the scope of use of the material.
[0004] Chinese patent application CN113831715A discloses a polycarbonate composite material, which uses phenyl glycidyl ether, bisphenol A diglycidyl ether, bisphenol A type epoxy resin, diimmonium carbide, and 2-oxazoline as hydrolysis resistance agents to improve the hydrolysis resistance of the composite material. However, under this solution, the above substances in the system cannot significantly improve the problem that the phosphate flame retardant is easily degraded and failed in a hot and humid environment.
[0005] Chinese patent application CN115232459A discloses an anti-ultraviolet PC / ABS alloy, in which the carboxylic acid-based ionomer can enhance the dispersion of the anti-ultraviolet agent, thereby achieving a significant improvement in the anti-ultraviolet performance. Summary of the invention
[0006] The invention provides a phosphate flame-retardant PC / ABS alloy with good resistance to moisture and heat aging. At the same time, the invention provides a preparation method and application of the PC / ABS alloy.
[0007] The present invention is achieved through the following technical solutions:
[0008] A PC / ABS alloy, comprising the following components in parts by weight:
[0009] PC resin 50-90 parts;
[0010] ABS resin 3-20 parts;
[0011] 5-20 parts of phosphate flame retardant;
[0012] 3-15 parts of carboxylic acid ionomer;
[0013] 0.05-1.5 parts of moisture and heat improving agent;
[0014] The weight ratio of the phosphate flame retardant to the moisture-heat modifier is in the range of (10-100):1;
[0015] The carboxylic acid-based ionomer is an ethylene / methacrylic acid copolymer, wherein 25 mol% to 89 mol% of the carboxyl groups in the methacrylic acid units are neutralized by metal ions.
[0016] Preferably, the weight ratio of the phosphate flame retardant to the moisture-heat improver is in the range of (15-30):1.
[0017] Preferably, the weight content of the carboxylic acid-based ionomer is 6-9 parts.
[0018] Preferably, in the carboxylic acid-based ionomer, 30 mol % to 44.9 mol % of the carboxyl groups in the methacrylic acid units are neutralized by metal ions.
[0019] The metal ion is selected from at least one of sodium ion, zinc ion, magnesium ion and potassium ion, preferably zinc ion, the melt index of the carboxylic acid ionomer is between 0.5-6g / 10min, the test conditions are 190°C, 2.16kg, and the test standard is ISO 1133-1. The carboxylic acid ionomer can be a commercial product or a homemade raw material. In order to more accurately illustrate the invention, the specific implementation of the invention adopts homemade raw materials.
[0020] The preparation method of the carboxylic acid-based ionomer is as follows: according to the calculated neutralization degree ratio, ethylene-methacrylic acid and Zn(CH3COO)2·2H2O (or sodium hydroxide, potassium hydroxide, magnesium hydroxide) are uniformly mixed and then extruded into granules through a twin-screw extruder, the screw temperature is 150-170°C, and the speed range is 150-350 r / min.
[0021] The moisture-heat improving agent is selected from at least one of phenyl glycidyl ether, bisphenol A diglycidyl ether, bisphenol A type epoxy resin, diimmonium carbide, and 2-oxazoline;
[0022] Preferably at least one of phenyl glycidyl ether and diimide carbodiimide;
[0023] Carbodiimide is more preferred.
[0024] It can be mentioned that the phosphate flame retardant is selected from at least one of triphenyl phosphate, bisphenol A-bis(diphenyl phosphate), and resorcinol bis(diphenyl phosphate), and bisphenol A-bis(diphenyl phosphate) is preferred from the perspective of notched impact strength.
[0025] The PC / ABS alloy of the present invention has no special requirements for polycarbonate resin and ABS resin. The PC resin can be bisphenol A polycarbonate, with a suitable melt index between 3-22 g / 10 min, and the test conditions are 300° C., 1.2 kg; the suitable melt index of ABS resin is between 7-24 g / 10 min, and the test conditions are 220° C., 10 kg, and the test standard is ISO 1133-1.
[0026] The preparation method of the PC / ABS alloy of the present invention comprises the following steps: mixing the components uniformly according to the proportion, extruding and granulating through a twin-screw extruder, with the screw speed ranging from 200 to 300 rpm and the temperature ranging from 210 to 260° C., to obtain the PC / ABS alloy.
[0027] The PC / ABS alloy of the present invention is used to prepare electrical parts (such as dishwasher controllers, mobile power supply housings) and other parts that need to have complex structures, flame retardancy, good resistance to moisture and heat aging, and the like.
[0028] The present invention has the following beneficial effects
[0029] The carboxylic acid-based ionomer itself is more easily dispersed on the surface of the alloy system. The moisture-heat modifier dispersed in the carboxylic acid-based ionomer forms a water molecule barrier layer / anti-hydrolysis layer on the surface of the workpiece. The carboxylic acid-based ionomer can significantly improve the ability to resist water penetration, and the moisture-heat modifier can improve the moisture-heat hydrolysis resistance of the carboxylic acid-based ionomer, thereby preventing the inward penetration of water molecules, thereby realizing the moisture-heat aging resistance of the phosphate flame-retardant PC / ABS alloy and achieving long-term flame retardancy. Implementation
[0030] The present invention is described in detail below in conjunction with specific embodiments. The following embodiments will help those skilled in the art to further understand the present invention, but are not intended to limit the present invention in any form. It should be noted that, for those of ordinary skill in the art, several variations and improvements may be made without departing from the concept of the present invention. These all belong to the protection scope of the present invention.
[0031] The sources of raw materials used in the present invention are as follows:
[0032] PC resin: PC WY-106BR, bisphenol A polycarbonate, melt index 6g / 10min (300℃, 1.2kg), Lihua Yiweiyuan Chemical Co., Ltd.
[0033] ABS resin: Chimei, ABS PA-757, melt index 18g / 10min (220℃, 10kg)
[0034] Carboxylic acid ionomer A: 25.0 mol% of the carboxyl groups in the methacrylic acid unit are neutralized by zinc metal ions, the melt index is between 1.6 g / 10 min, the test conditions are 190 ° C, 2.16 kg, homemade;
[0035] Carboxylic acid ionomer B: 30.1 mol% of the carboxyl groups in the methacrylic acid unit are neutralized by zinc metal ions, the melt index is between 1.9 g / 10 min, the test conditions are 190 ° C, 2.16 kg, homemade;
[0036] Carboxylic acid ionomer C: 35.1 mol% of the carboxyl groups in the methacrylic acid unit are neutralized by zinc metal ions, the melt index is between 3.1 g / 10 min, the test conditions are 190 ° C, 2.16 kg, homemade;
[0037] Carboxylic acid ionomer D: 39.9 mol% of the carboxyl groups in the methacrylic acid unit are neutralized by zinc metal ions, the melt index is between 2.4 g / 10 min, the test conditions are 190 ° C, 2.16 kg, homemade;
[0038] Carboxylic acid ionomer E: 44.9 mol% of the carboxyl groups in the methacrylic acid unit are neutralized by zinc metal ions, the melt index is between 2.0 g / 10 min, the test conditions are 190 ° C, 2.16 kg, homemade;
[0039] Carboxylic acid ionomer F: 88.9 mol% of the carboxyl groups in the methacrylic acid unit are neutralized by zinc metal ions, the melt index is between 3.5 g / 10 min, the test conditions are 190 ° C, 2.16 kg, homemade;
[0040] Carboxylic acid ionomer G: 40 mol% of the carboxyl groups in the methacrylic acid unit are neutralized by magnesium metal ions, the melt index is between 2.4 g / 10 min, the test conditions are 190 ° C, 2.16 kg, homemade;
[0041] Carboxylic acid ionomer H: 40 mol% of the carboxyl groups in the methacrylic acid unit are neutralized by potassium metal ions, the melt index is between 1.9 g / 10 min, the test conditions are 190 ° C, 2.16 kg, homemade;
[0042] Carboxylic acid ionomer I: 20 mol% of the carboxyl groups in the methacrylic acid unit are neutralized by zinc metal ions, the melt index is between 2.6 g / 10 min, the test conditions are 190 ° C, 2.16 kg, homemade;
[0043] Carboxylic acid ionomer J: 95 mol% of the carboxyl groups in the methacrylic acid unit are neutralized by zinc metal ions, the melt index is between 3.3 g / 10 min, the test conditions are 190 ° C, 2.16 kg, homemade;
[0044] Triphenyl phosphate: WSFR-TPP, Zhejiang Wansheng Technology Co., Ltd.;
[0045] Bisphenol A-bis(diphenyl phosphate): WSFR-BDP-N2, Zhejiang Wansheng Technology Co., Ltd.;
[0046] Resorcinol bis(diphenyl phosphate): WSFR-RDP, Zhejiang Wansheng Technology Co., Ltd.;
[0047] Diimmonium carbodiide: Stabilizer 7000, Raschig, Germany;
[0048] Phenyl glycidyl ether: Changzhou Hongyu Chemical Co., Ltd.;
[0049] Bisphenol A diglycidyl ether: Hubei Shishun Biotechnology Co., Ltd.;
[0050] Bisphenol A epoxy resin: Shanghai Aladdin Biochemical Technology Co., Ltd.;
[0051] 2-Oxazoline: Hubei Qianmosheng Biotechnology Co., Ltd.;
[0052] Embodiment and comparative example PC / ABS alloy preparation method: according to the ratio, each component is mixed evenly, and granulated by extrusion through a twin-screw extruder, the screw speed range is 250-350 rpm, and the temperature is set at 200-260° C. to obtain PC / ABS alloy.
[0053] Various test methods:
[0054] (1) Flame retardancy: 1.5 mm flame retardant specimens were tested according to UL 94-2018 method.
[0055] (2) Long-term flame retardancy under moisture and heat aging: Prepare 1.5 mm flame retardant specimens according to UL 94-2018 conditions, and test the flame retardancy after aging at 85°C / 85% humidity for 1000h / 2000h.
[0056] (3) Notched impact strength: Notched impact strength is tested at room temperature according to ISO 180-2000 standard.
[0057] Table 1: Content of each component (parts by weight) and test results of PC / ABS alloys in Examples 1-7
[0058] Example 1 Example 2 Example 3 Example 4 Example 5 Example 6 Example 7 PC resin 70 70 70 70 50 60 90 ABS resin 10 10 10 10 3 8 20 Carboxylate Ionomer A 3 6 9 15 8 10 15 Bisphenol A-bis(diphenyl phosphate) 10 10 10 10 5 8 20 Diimmonium carbide 0.5 0.5 0.5 0.5 0.05 0.15 0.2 Flame retardant V-0 V-0 V-0 V-0 V-0 V-0 V-0 Long-term flame retardancy 1000h V-0 V-0 V-0 V-0 V-0 V-0 V-0 Long-term flame retardancy 2000h V-1 V-0 V-0 V-0 V-1 V-0 V-0 <![CDATA[Notched impact strength, kJ / m 2 > 56 53 48 43 30 35 37
[0059] It can be seen from Examples 1-4 that the preferred carboxylic acid ionomer content is 6-9 parts to achieve the improvement of long-term flame retardancy and maintain good notched impact strength.
[0060] Table 2: Content of each component (parts by weight) and test results of PC / ABS alloys in Examples 8-14
[0061] Example 8 Example 9 Example 10 Embodiment 11 Example 12 Embodiment 13 Embodiment 14 PC resin 70 70 70 70 70 70 70 ABS resin 10 10 10 10 10 10 10 Carboxylic acid ionomer types B C D E F G H Carboxylic acid ionomer content 3 3 3 3 3 3 3 Bisphenol A-bis(diphenyl phosphate) 10 10 10 10 10 10 10 Diimmonium carbide 0.5 0.5 0.5 0.5 0.5 0.5 0.5 Flame retardant V-0 V-0 V-0 V-0 V-0 V-0 V-0 Long-term flame retardancy 1000h V-0 V-0 V-0 V-0 V-1 V-0 V-0 Long-term flame retardancy 2000h V-0 V-0 V-0 V-0 V-1 V-0 V-0 <![CDATA[Notched impact strength, kJ / m 2 > 58 61 58 56 42 45 48
[0062] As can be seen from Examples 1 / 8-14, it is preferred that the carboxylic acid-based ionomers have 30 mol%-44.9 mol% of the carboxyl groups in the methacrylic acid units neutralized by metal ions. As can be seen from Examples 10 / 13 / 14, the metal ions are preferably zinc ions.
[0063] Table 3: Content of each component (parts by weight) and test results of PC / ABS alloys in Examples 15-19
[0064] Embodiment 15 Example 16 Embodiment 17 Embodiment 18 Embodiment 19 PC resin 70 70 70 70 70 ABS resin 10 10 10 10 10 Carboxylate Ionomer A 3 3 3 3 6 Bisphenol A-bis(diphenyl phosphate) 10 10 10 10 10 Diimmonium carbide 1 0.67 0.33 0.2 0.1 Flame retardant V-0 V-0 V-0 V-0 V-0 Long-term flame retardancy 1000h V-0 V-0 V-0 V-1 V-1 Long-term flame retardancy 2000h V-0 V-0 V-0 V-1 V-2 <![CDATA[Notched impact strength, kJ / m 2 > 55 56 55 57 56
[0065] It can be seen from Examples 1 / 15-19 that the preferred weight ratio of the phosphate flame retardant to the moisture-heat improver is (15-30):1, and the moisture-heat aging resistance and long-term flame retardancy are better.
[0066] Table 4: Content of each component (parts by weight) and test results of PC / ABS alloys in Examples 20-25
[0067] Embodiment 20 Embodiment 21 Embodiment 22 Embodiment 23 Embodiment 24 Embodiment 25 PC resin 70 70 70 70 70 70 ABS resin 10 10 10 10 10 10 Carboxylate Ionomer A 6 6 6 6 6 6 Bisphenol A-bis(diphenyl phosphate) 10 10 10 10 Triphenyl phosphate 10 Resorcinol bis(diphenyl phosphate) 10 Diimmonium carbide 0.5 0.5 Phenyl glycidyl ether 0.5 Bisphenol A diglycidyl ether 0.5 Bisphenol A epoxy resin 0.5 2-Oxazoline 0.5 Flame retardant V-0 V-0 V-0 V-0 V-0 V-0 Long-term flame retardancy 1000h V-0 V-0 V-0 V-1 V-1 V-1 Long-term flame retardancy 2000h V-0 V-0 V-1 V-1 V-1 V-1 <![CDATA[Notched impact strength, kJ / m 2 > 49 47 48 44 45 36
[0068] It can be seen from Examples 2 / 20-21 that the flame retardant is preferably bisphenol A-bis(diphenyl phosphate), which has a higher notched impact strength.
[0069] It can be seen from Examples 2 / 22-25 that the moisture-heat improving agent is preferably at least one of phenyl glycidyl ether and diimide carbodiimide; diimide carbodiimide is more preferred.
[0070] Table 5: Comparative Example PC / ABS alloy component content (parts by weight) and test results
[0071] Comparative Example 1 Comparative Example 2 Comparative Example 3 Comparative Example 4 Comparative Example 5 PC resin 70 70 70 70 70 ABS resin 10 10 10 10 10 Carboxylate Ionomer A 0 1 20 10 10 Bisphenol A-bis(diphenyl phosphate) 10 10 10 10 10 Diimmonium carbide 0.5 0.5 0.5 0 2 Flame retardant V-0 V-0 V-1 V-0 V-0 Long-term flame retardancy 1000h The V-2 could not reach The V-2 could not reach The V-2 could not reach V-2 V-2 Long-term flame retardancy 2000h The V-2 could not reach The V-2 could not reach The V-2 could not reach The V-2 could not reach The V-2 could not reach <![CDATA[Notched impact strength, kJ / m 2 > 58 55 27 44 39
[0072] It can be seen from Comparative Examples 1 / 2 that without adding carboxylic acid-based ionomer or with too low a content, the long-term flame retardancy against moist heat aging is poor.
[0073] From the comparative example 3, if the carboxylic acid-based ionomer content is too high, not only the resistance to moisture and heat aging and long-term flame retardancy are poor, but also the notched impact strength decreases too much.
[0074] It can be seen from Comparative Example 5 that if the content of the moisture-heat modifier is too high, the moisture-heat aging resistance and long-term flame retardancy are poor, and the notched impact strength is also greatly reduced.
Claims
1. A PC / ABS alloy, characterized in that: By weight, it includes the following components: PC resin 50-90 parts; ABS resin 3-20 parts; 5-20 parts of phosphate flame retardant; 3-15 parts of carboxylic acid ionomer; 0.05-1.5 parts of moisture and heat improving agent; The weight ratio of the phosphate flame retardant to the moisture-heat modifier is in the range of (10-100):1; The carboxylic acid-based ionomer is an ethylene / methacrylic acid copolymer, wherein 25 mol% to 89 mol% of the carboxyl groups in the methacrylic acid units are neutralized by metal ions; The moisture-heat improving agent is selected from at least one of phenyl glycidyl ether, bisphenol A diglycidyl ether, bisphenol A type epoxy resin, carbodiimide, and 2-oxazoline.
2. The PC / ABS alloy according to claim 1, characterized in that: The weight ratio of the phosphate flame retardant to the moisture-heat improver is in the range of (15-30):
1.
3. The PC / ABS alloy according to claim 1, characterized in that: The weight content of the carboxylic acid-based ionomer is 6-9 parts.
4. The PC / ABS alloy according to claim 1, characterized in that: 30 mol % to 44.9 mol % of the carboxyl groups in the methacrylic acid units in the carboxylic acid-based ionomer are neutralized by metal ions.
5. The PC / ABS alloy according to claim 1, characterized in that: The metal ion is selected from at least one of sodium ion, zinc ion, magnesium ion and potassium ion. The melt index of the carboxylic acid-based ionomer is between 0.5-6 g / 10 min. The test conditions are 190° C. and 2.16 kg.
6. The PC / ABS alloy according to claim 5, characterized in that: The metal ions are selected from zinc ions.
7. The PC / ABS alloy according to claim 1, characterized in that: The moisture-heat improving agent is selected from at least one of phenyl glycidyl ether and carbodiimide.
8. The PC / ABS alloy according to claim 7, characterized in that: The moisture-heat improving agent is selected from carbodiimide.
9. The PC / ABS alloy according to claim 1, characterized in that: The phosphate flame retardant is selected from at least one of triphenyl phosphate, bisphenol A-bis(diphenyl phosphate), and resorcinol bis(diphenyl phosphate).
10. The PC / ABS alloy according to claim 9, characterized in that: The phosphate flame retardant is selected from bisphenol A-bis(diphenyl phosphate).
11. The PC / ABS alloy according to claim 1, characterized in that: The PC resin is selected from bisphenol A polycarbonate, the melt index is between 3-22g / 10min, and the test conditions are 300°C and 1.2kg; the melt index of ABS resin is between 7-24g / 10min, and the test conditions are 220°C and 10kg.
12. The method for preparing the PC / ABS alloy according to any one of claims 1 to 11, characterized in that: The method comprises the following steps: mixing the components uniformly according to the proportion, extruding and granulating through a twin-screw extruder, wherein the screw speed range is 200-300 rpm and the temperature range is 210-260° C., so as to obtain a PC / ABS alloy.
13. Application of the PC / ABS alloy according to any one of claims 1 to 11, characterized in that: Used to prepare electrical parts.
Citation Information
Patent Citations
Polycarbonate composite material as well as preparation method and application thereof
CN113831715A
Efficient reinforced halogen-free flame retardant functional master batch for direct injection molding of PBT and preparation method of efficient reinforced halogen-free flame retardant functional master batch
CN109370175A
Anti-ultraviolet PC / ABS alloy as well as preparation method and application thereof
CN115232459A